TARP and the long-term perception of risk - Semaan, Elias; Drake, Pamela Peterson (Journal of Banking & Finance, 2016)
The Capital Purchase Program (CPP) was intended to enhance capital and preserve lending capacity of banks, but the role of this program in affecting the risk of participating banks has been unresolved. We address this issue by investigating the market’s long-term perception of risk for financial institutions participating in the CPP. Leading up to and including the crisis, the systematic and idiosyncratic variances of the stock returns of all financial firms increased; following CPP, the relative idiosyncratic risk of CPP participants remained higher than for those not participating in CPP for four years following CPP.